(untitled) (Między Oryginałem a Przekładem, 2019)
Denotation – Humour – Taboo This analysis takes as its subject jokes about Poles that appeared in two US-American sitcoms: The Big Bang Theory (Teoria wielkiego podrywu) and 2 Broke Girls (Dwie spłukane dziewczyny), as well as their official Polish TV translations made for Comedy Central Polska channel. The selected examples refer to Polish traditions, history, and stereotypes about Polish people. They were divided into three categories according to their subject: a joke based on a stereotype, jokes making Poles look exotic, and jokes referring to Polish-Jewish relations, and the history of World War II. The aim here is accordingly: to characterize the original jokes, to analyze their official Polish voice-over translation, and to consider the potential differences in the reception of given fragments by the sourceculture and target-culture viewers. This paper refers to the characteristics of sitcom as a text genre and Eugene A. Nida and Charlesa R. Taber’s theory of functional equivalence.